Do people vote for education? evidence from Brazilian municipal elections - Assunção, Matheus de Mello de (2016)
Basic education is widely cited in the literature in economics as an essential factor to the development of a country. Moreover, by the externalities it generates, it is seen as a service whose optimal supply requires public financing or provision. In Brazil, as in other countries, basic education is constitutionally established as responsibility of states and municipalities. The demand of voters for education, however, is unknown. This paper seeks to fill this gap by estimating the impact of a change in municipal spending on basic education in the reelection chances of a mayor. For that, it uses as variation the federal transfers from the Fund for the Maintenance and Development of Fundamental Education and Valuing of Teachers (FUNDEF). In addition, it evaluates possible channels through which spending can bring political returns such as level of teacher training and infrastructure of schools.